Health Education and Applying Appropriate Technology for Instant Ginger Milk in PKK Gonggangan - Fauzi, Ahmad; Saifudin, Azis; Hidayatullah, Muhammad Haqqi; Amanda, Pramaisshela Rizvya (Jurnal Inovasi Sains dan Teknologi Untuk Masyarakat, 2026)
Inappropriate use of household medicine poses risks of side effects, adverse interactions, and hazards due to improper storage and disposal. This education activity was conducted to increase public knowledge and awareness regarding the DAGUSIBU (Get, Use, Save, Dispose) concept among members of the PKK group in Gonggangan Hamlet, Bolon, Colomadu, Karanganyar, Central Java. The materials provided included how to obtain medicine from official facilities such as pharmacies, usage according to dosage and indication, correct storage to maintain stability, and safe and responsible disposal of expired medicine . The delivery method consisted of interactive presentations and discussions, followed by training on the application of appropriate technology for producing instant ginger milk made from fresh ginger, lemongrass, cloves, cinnamon, cardamom, sugar, and fresh cow's milk. This training aimed to enhance skills based on local potential while opening opportunities for small and medium enterprises. Evaluation using pre-post tests showed an increase in average knowledge scores from 62.5 to 87.3 (+ 39.68%), with 90.6% of participants stating they would apply this knowledge in their daily lives. Some participants also expressed interest in developing the production of instant ginger milk for family consumption and local sales. The results indicated that DAGUSIBU education is effective in increasing awareness of proper medicine use, while appropriate technology-based training triggers entrepreneurial motivation. The combination of these two activities is expected to encourage independence in maintaining family health while improving the economic welfare of their households.